Identification of potential amino acids profile with the protein expression of idh1, mgmt, atrx and oxidative stress markers in the primary brain tumour - Ling, Michelle Tiong Hui (2025)
Primary central nervous system (CNS) tumours are heterogeneous neoplasms originating within the CNS, each category exhibiting distinct histological and molecular features that influence clinical progression and prognosis. Protein alterations are central to CNS tumour development, involving IDH1, ATRX, MGMT, CAT, and SOD1, alongside amino acid disruptions as key contributors to tumour progression. This study aimed to determine the amino acid profile and expression patterns of ATRX, MGMT, IDH1, 1p/19q, CAT, and SOD1 in primary CNS tumours. Amino acid profiles were characterised using gas chromatography-mass spectrometry (GCMS), protein expression of IDH1, ATRX, MGMT, CAT, and SOD1 was evaluated using immunohistochemistry (IHC), and the fluorescence in situ hybridization (FISH) protocol for 1p/19q co-deletion was optimised. GCMS analysis identified 11 amino acids across 40 FFPE CNS tumour samples. IHC revealed ATRX expression in 65% (26 cases), MGMT in 67.5% (27 cases), IDH1 in 27.5% (11 cases), CAT in 67.5% (27 cases), and SOD1 in all cases (100%), with significant associations between marker expression, tumour grade, and type (p < 0.001). The optimised FISH protocol successfully detected 1p/19q co-deletion in 2 oligodendroglioma cases, with negative co-deletion in 2 anaplastic astrocytoma and positive co-deletion in 1 glioblastoma case. These findings provide new insights into amino acid profiling and the expression of ATRX, MGMT, IDH1, CAT, dan SOD1 proteins in primary CNS tumours. Further research is warranted to expand on these results, contributing to a deeper understanding of tumour biology and the potential identification of novel diagnostic and therapeutic biomarkers